Representasi Konsep Diri Remaja Perempuan Pembaca Buku “Sebuah Seni Untuk Bersikap Bodo Amat” dari Mark Manson - Canesya Adzani; Gregorius Genep Sukendro (Koneksi, 2020)
Adolescence is a time of self-identification and self-development. The view of oneself that had developed in childhood strengthened in adolescence. This is in line with increasing age and life experience based on the facts experienced. All that makes teenagers can judge themselves good, and also vice versa, less good. Teenagers tend to look at the social media profiles of other teenagers and make comparisons with themselves. This comparison will unconsciously form an ideal self-concept whose standards are getting higher and further away from the self-concept possessed by adolescents today. Teenagers who get negative feedback from social media will find it difficult to accept themselves. There is always an assumption that other people around him will look negatively towards him. The question in this study is "What is the representation of the self-concept of young women readers of the book The Subtle Art of Not Giving a F*ck?". The results based on this study explain that self-concept in adolescent girls after reading The Subtle Art of Not Giving a F*ckis represented as a person who needs to direct himself towards self-help and self-love by realizing how good or bad the situation is owned and how obliged to behave against the situation. The representation of self-help and self-love in the self-concept of the reader is depicted using trying not to think about the affairs of others and focus more on oneself, controlling oneself, accepting and trying to solve cases of life in a cruel global world, and knowing what important are priorities.Usia remaja merupakan tahap pengembangan diri. Pengetahuan tentang diri sendiri yang telah berkembang pada masa anak-anak makin menguat pada masa remaja. Hal ini berbarengan dengan bertambahnya usia dan pengalaman atas dasar kehidupan yang dialami. Semua itu menciptakan remaja yang mampu menilai dirinya sendiri baik, dan juga sebaliknya, kurang baik. Remaja cenderung akan melihat profil remaja lain dan melakukan perbandingan menggunakan dirinya. Perbandingan ini secara tidak sadar akan membangun konsep diri ideal yang standarnya semakin tinggi dan semakin jauh menurut konsep diri yang dimiliki oleh remaja saat ini. Remaja yang mendapatkan reaksi negatif akan sulit mendapat dirinya sendiri. Muncul anggapan bahwa orang lain disekitarnya akan memandang negatif terhadap dirinya. Pertanyaan dalam penelitian ini adalah bagaimana representasi konsep diri remaja perempuan pembaca buku perbaikan diri “Sebuah Seni Untuk Bersikap Bodo Amat”? Hasil penelitian ini menunjukkan bahwa konsep diri pada remaja perempuan setelah membaca buku “Sebuah Seni Untuk Bersikap Bodo Amat” direpresentasikan menjadi suatu pribadi yang perlu mengarahkan dirinya menuju self-help dan self-lovedengan mengetahui seberapa baik atau tidak baik keadaan yang dimiliki dan bagaimana wajib bersikap terhadap keadaan tersebut. Representasi self-help danself-lovepada konsep diri pembacanya digambarkan dengan berusaha untuk tidak memikirkan urusan orang lain dan lebih fokus pada diri sendiri, mengontrol diri, menerima dan berusaha memecahkan kasus hidup di dunia yang kejam, dan mengetahui apa yang penting sebagai prioritas.